Exploring Students’ Perceptions of the Impact of Computer Multimedia on Their Teachers’ Motivation - Khaled Ahmed Aqeel Alzoubi (Scientia Publica Media, 2025)
Educational media is launched, and it means all the tools used to make the teaching and learning process successful, from audible speeches and written texts, and all visuals from drawings, data, still and moving images. In general, it is called everything that can act as a mediator between a teacher and a learner, or represents a cognitive outlet to pass a message or educational content. The most important development issues that form the basis of the progress of societies and their ability to face the many and accelerating challenges they face are preparing teachers and increasing and enhancing their motivation towards education in a manner that is consistent with the requirements of the current era. The challenges facing the world’s societies are large and multiple, and it is difficult to predict their size and the extent of their impact. They are characterized by being deeper and more complex, so we must keep pace with current global developments by preparing an individual capable of creativity and development. Motivating teachers increases the performance of their duties and helps teachers discover the educational difficulties facing students and the ability to control, overcome and address them. Therefore, this study aimed to explore the relationship between the motivation of mathematics teachers through computer multimedia and students’ perceptions. To collect quantitative and qualitative data to know students’ perceptions of teachers’ motivation, the researcher conducted a questionnaire that included 12 mathematics teachers and 407 randomly selected students. The researcher used the Likert scale in his study, and to collect and analyze the data, the descriptive approach was used, and the SPSS program was adopted to analyze the results and hypotheses. The results showed that computer multimedia increases mathematics teachers’ motivation according to students’ perceptions.